PENENTUAN KARYAWAN TERBAIK DENGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING PADA PERUSAHAAN KONTRAKTOR - Bella Jenni Ourelia; Fransiska Prihatini Sihotang (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
PT MPR is company that run in contractor industry. One of aspect that important is company human resource management employee performance assessment. This company use employee performance assessment, but when using it theres still some problem when calculating progress it take little bit time because theres a lot of employee in the company and the result of calculating not really accurate because of manual calculating. The purpose developing this decission support system in PT MPR is to helping HRD deciding who’s the best employee on company, so when calculating evaluation doesn’t take a lot of time and faster also accurate. Methodology developing this system using Rational Unified Process (RUP) that contain inception, elaboration, construction and transition. Methodology decision support using Simple Additive Weighting (SAW). Application made using website based and using visual studio code, programming language using PHP and MySQL. Thats why writer help solving problem with developing this decision support system for choosing the best employee with using SAW method